2020
DOI: 10.1111/boer.12236
|View full text |Cite
|
Sign up to set email alerts
|

How does public spending affect technical efficiency? Some evidence from 15 European countries

Abstract: The relationship between government size and economic growth has been widely debated. Revisiting the subject from a distinct angle with respect to the mainstream approach, we provide an empirical analysis of the impact of government size on technical efficiency. The aim of this paper is to estimate the impact of public sector's size and of public expenditure components on 15 European countries' technical efficiency from 1996 to 2014 by using a True Random Effect model. Using the total public expenditure as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…So nearly 90% of the variation in per capita health expenditure in 13 countries is explained by the variation in per capita GDP [ 29 , 30 ]. Numerous subsequent papers corroborate the empirical evidence of the link between aggregate income and health expenditure [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. These findings have been generalised in studies in European Union countries, in the G7 and the Seven Emerging Markets (EM7) [ 50 ], in the 15 member countries of the Economic Community of West African States (ECOWAS) [ 51 ], and in countries as politically and socially distant as China and the United States [ 52 ].…”
Section: Discussionmentioning
confidence: 70%
“…So nearly 90% of the variation in per capita health expenditure in 13 countries is explained by the variation in per capita GDP [ 29 , 30 ]. Numerous subsequent papers corroborate the empirical evidence of the link between aggregate income and health expenditure [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. These findings have been generalised in studies in European Union countries, in the G7 and the Seven Emerging Markets (EM7) [ 50 ], in the 15 member countries of the Economic Community of West African States (ECOWAS) [ 51 ], and in countries as politically and socially distant as China and the United States [ 52 ].…”
Section: Discussionmentioning
confidence: 70%
“…They also showed that expenditures on defence, economic affairs, general public services and social protection have negative effects. Auci et al (2020) received similar findings for technical efficiency, a component of total factor productivity (TFP), using a true random effect (RE) model for 15 European countries. Our results for labour productivity resemble the Lupu et al and Auci et al findings for military expenditures and social protection.…”
Section: Introductionmentioning
confidence: 63%
“…The most relevant works for our study are those of Lupu et al (2018) and Auci et al (2020). Using time-series analysis, Lupu et al found positive effects of expenditures on education and healthcare on economic growth in Central and Eastern European countries.…”
Section: Introductionmentioning
confidence: 99%
“…Public spending is also likely to be related to the level of firms’ technical efficiency, as it affects the overall institutional environment. Thus, Auci et al (2021) find evidence of a strong association between the size and the type of public expenditure and the aggregate technical efficiency levels of the European economies. In a study of Mexican municipalities, Becerra-Ornelas and Nunez (2019) examine the effect of public spending on technical efficiency of the local production and find a negative association between the two irrespectively of the expenditure type.…”
Section: The Estimation Of Technical Efficiency Levels and Their Dete...mentioning
confidence: 83%